Criminal Act of Utilization of Forest Products for Debt Payment (Review of Decision of Kendari District Court Number 495/Pid.Sus/2022/Pn Kdi.) - Ramanda, Lutfhy Ramanda Ponco Wirando; Nur Kholim (DE'RECHTSSTAAT, 2025)
This article examines the criminal act of utilizing forest products to pay debts, which is a form of illegal exploitation of natural resources, especially forests, with the aim of fulfilling personal or corporate financial obligations. This research is descriptive-analytical, using a juridical-normative approach method that focuses on the study of laws and regulations, namely Law Number 41 of 1999 concerning Forestry, which was amended by Law Number 18 of 2013 concerning the Prevention and Eradication of Forest Destruction, and related criminal laws. The results of the study indicate that the criminal act of utilizing forest products to pay debts is a violation of forestry law provisions, even though it is motivated by personal economic reasons or financial needs. In this case, the theory of punishment prioritizes the objectives of rehabilitation, prevention, and deterrence for perpetrators, as well as protection of the environment and society. Although laws and regulations already exist, the main challenges in their implementation are weak law enforcement, lack of coordination between institutions, and the rampant illegal practices that are difficult to monitor. This paper recommends increased monitoring, stakeholder education and law enforcement, and the use of technology to detect forest destruction quickly and accurately.